2013
DOI: 10.1063/1.4773098
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling resonances in systems without a classical trapping

Abstract: Abstract:In this paper we analyze a free quantum particle in a straight Dirichlet waveguide which has at its axis two Dirichlet barriers of lengths ℓ ± separated by a window of length 2a. It is known that if the barriers are semiinfinite, i.e. we have two adjacent waveguides coupled laterally through the boundary window, the system has for any a > 0 a finite number of eigenvalues below the essential spectrum threshold. Here we demonstrate that for large but finite ℓ ± the system has resonances which converge t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The method also works without this assumption, however, the argument is more complicated [BE07]. Moreover, by the same technique one can also treat resonances: an example of a guide in which there are two long but finite Dirichlet barriers separating the Neumann window from semi-infinite Neumann boundary segments has been worked out in [BEG13]. 2.…”
Section: Notesmentioning
confidence: 99%
“…The method also works without this assumption, however, the argument is more complicated [BE07]. Moreover, by the same technique one can also treat resonances: an example of a guide in which there are two long but finite Dirichlet barriers separating the Neumann window from semi-infinite Neumann boundary segments has been worked out in [BEG13]. 2.…”
Section: Notesmentioning
confidence: 99%
“…The study of the resonances of the operator H ℓ emerging in the vicinity of the point λ 0 is reduced first to a special operator equation and then we show that these resonances coincide with the zeroes of certain holomorphic function. Our scheme is based on approach suggested in work [6], but there are serious modification due to a much more general formulation of the problem.…”
Section: Resonances As Zeroes Of a Holomorphic Functionmentioning
confidence: 99%
“…They can be situations, when only finitely many resonances emerge from a point in the essential spectrum. This was the case in [6], where a Laplacian was considered in the strip with a combination of Dirichlet and Neumann conditions imposed so that the final model could be regarded as an operator with three distant perturbations and the central perturbation had a simple isolated discrete eigenvalue λ 0 embedded into the essential spectrum of the left and right perturbations. It was shown that the original operator had one resonance converging to λ 0 and the leading terms in its asymptotics were found.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [9], there was studied a problem for the Laplacian in the strip, where the distant perturbations were replaced by the Dirichlet and Neumann boundary conditions. A similar problem but in a multi-dimensional cylinder was studied in [1].…”
Section: Introductionmentioning
confidence: 99%
“…In all studied models, in the case, when the resonances and/or eigenvalues emerged and accumulated along some segment in the essential spectrum, their asymptotics were also power with respect to the distance between the distant potentials [6], [12], [13], [21], [24]. In the case of perturbing the eigenvalues embedded into the essential spectrum, only finitely many resonances with exponential asymptotics arose [1], [9], [14]. This poses a natural question: whether this is true that the emergence of infinitely many resonances means that they always have power in the distance asymptotics, while in the case of emergence of finitely many resonances the corresponding asymptotics are always exponential?…”
Section: Introductionmentioning
confidence: 99%